Cooperative advertising and quantity discount in manufacturer-retailer supply chains. (17th May 2021) - Zaheri, Amin; Rafiee, Majid; Kayvanfar, Vahid
Abstract : Purpose: This paper aims to study the impact of existence and lack of discount on the relationships between one manufacturer and one retailer under the cooperative and the non-cooperative games and the members' profits are compared. Design/methodology/approach: In the first approach, the manufacturer's price function is constant, and in the second approach, this price function is a decreasing function with respect to lot size. These approaches are modeled through three games structure, including two Stackelberg games and one cooperative game. Findings: Some numerical instances comprising sensitivity analysis are provided, and then the members' profits in different scenarios are compared. This paper reveals that in the presented models, whether the members are inclined to change their profits. Practical implications: This paper presents a tool of decision-making for the type of relationships of members in two different circumstances, and an approach is also presented to maximize the members' profit. Originality/value: In this paper, the relationships between one manufacturer and one retailer are studied under six different circumstances, where pricing, cooperative advertising and inventory cost are considered simultaneously. Also, a different model is presented to make a balance in individual profits and gain more profit for each member compared to the cooperative and non-cooperative game.